Steroid regulation: An overlooked aspect of tolerance and chronic rejection in kidney transplantation. (15th September 2018) - Christakoudi, Sofia; Runglall, Manohursingh; Mobillo, Paula; Rebollo-Mesa, Irene; Tsui, Tjir-Li; Nova-Lamperti, Estefania; Norris, Sonia; Kamra, Yogesh; Hilton, Rachel; Bhandari, Sunil; Baker, Richard; Berglund, David; et al.
Abstract: Steroid conversion ( HSD11B1, HSD11B2, H6PD ) and receptor genes ( NR3C1, NR3C2 ) were examined in kidney-transplant recipients with "operational tolerance" and chronic rejection (CR), independently and within the context of 88 tolerance-associated genes. Associations with cellular types were explored. Peripheral whole-blood gene-expression levels (RT-qPCR-based) and cell counts were adjusted for immunosuppressant drug intake. Tolerant (n = 17), stable (n = 190) and CR patients (n = 37) were compared. Healthy controls (n = 14) were used as reference. The anti-inflammatory glucocorticoid receptor ( NR3C1 ) and the cortisol-activating HSD11B1 and H6PD genes were up-regulated in CR and were lowest in tolerant patients. The pro-inflammatory mineralocorticoid gene ( NR3C2 ) was downregulated in stable and CR patients. NR3C1 was associated with neutrophils and NR3C2 with T-cells. Steroid conversion and receptor genes, alone, enabled classification of tolerant patients and were major contributors to gene-expression signatures of both, tolerance and CR, alongside known tolerance-associated genes, revealing a key role of steroid regulation and response in kidney transplantation. Highlights: Steroid conversion and receptor genes in blood are altered in kidney transplantation. Steroid activation ( HSD11B1, H6PD ) and response ( NR3C1 ) are not increased in tolerance. Upregulated NR3C1 and HSD11B1 indicate unmet cortisol demand in chronic rejection. Drug-adjusted NR3C1 expression is associated with neutrophils and NR3C2 with T-cells. Drug adjustment enables evaluation of endogenous factors influencing gene expression.